IL-4-dependent Jagged1 expression/processing is associated with survival of chronic lymphocytic leukemia cells but not with Notch activation. Issue 12 (December 2018) - De Falco, Filomena; Del Papa, Beatrice; Baldoni, Stefano; Sabatini, Rita; Falzetti, Franca; Di Ianni, Mauro; Martelli, Maria; Mezzasoma, Federica; Pelullo, Maria; Marconi, Pierfrancesco; Sportoletti, Paolo; Screpanti, Isabella; et al.
Abstract As previously reported, chronic lymphocytic leukemia (CLL) cells show constitutive Notch1/2 activation and express the Notchligand Jagged1. Despite increasing knowledge of the impact of Notch alterations on CLL biology and pathogenesis, the role of Jagged1 expressed in CLL cells remains undefined. In other cell types, it has been shown that after Notch engagement, Jagged1 not only activates Notch in signal-receiving cell, but also undergoes proteolytic activation in signal-sending cell, triggering a signaling with biological effects. We investigated whether Jagged1 expressed in CLL cells undergoes proteolytic processing and/or is able to induce Notch activation through autocrine/paracrine loops, focusing on the effect that CLL prosurvival factor IL-4 could exert on the Notch-Jagged1 system in these cells. We found that Jagged1 was constitutively processed in CLL cells and generated an intracellular fragment that translocated into the nucleus, and an extracellular fragment released into the culture supernatant. IL-4 enhanced expression of Jagged1 and its intracellular fragments, as well as Notch1/2 activation. The IL-4-induced increase in Notch1/2 activation was independent of the concomitant upregulated Jagged1 levels. Indeed, blocking Notch-Jagged1 interactions among CLL cells with Jagged1 neutralizing antibodies did not affect the expression of the Notch target Hes1. Notably, anti-Jagged1 antibodies partially prevented the IL-4-induced increase in Jagged1 processing and cell viability, suggesting that Jagged1 processing is one of the events contributing to IL-4-induced CLL cell survival. Consistent with this, Jagged1 silencing by small interfering RNA partially counteracted the capacity of IL-4 to promote CLL cell survival. Investigating the pathways whereby IL-4 promoted Notch1/2 activation in CLL cells independent of Jagged1, we found that PI3Kδ/AKT and PKCδ were involved in upregulating Notch1 and Notch2 proteins, respectively. Overall, this study provides new insights into the Notch-ligand system in CLL cells and suggests that targeting this system may be exploited as a novel/additional therapy approach for CLL.